Multiply by

**r**: 1 - 1/2**r**^2 = 3/5**r**1/2**r**^2 + 3/5**r**- 1 = 0 5**r**^2 + 6r - 10 = 0 And solve using the quadratic equation.3 Answe

**r**s · Science & Mathematics · 05/08/2009[(

**r**-2)(**r**+9) -2r(**r**+2)] / [(**r**+2)(**r**+9)] = 6 (**r**^2 + 7r -18 -2r^2 - 4r) / [(**r**+2)(**r**+9)] = 6 (-**r**^2 + 3r - 18) / (**r**^2 + 11r + 18) = 6 -**r**^2 + 3r - 18 = 6(**r**^2 + 11r + 18) = 6r^2 + 66r + 108 7r...1 Answe

**r**s · Science & Mathematics · 06/05/2010assume

**r**is any numbe**r**. {**r**∈ ℝ } as x becomes sufficiently close to that numbe**r**, f(x) becomes a**r**bit**r**a**r**ily close to f(**r**). fo**r**example: say**r**= 7 which means: f(**r**) = f(7) as x app**r**oaches...1 Answe

**r**s · Science & Mathematics · 14/10/2013**R**=(ab)/(a+b)**R**(a+b) = ab Ra + Rb = ab Rb = ab - Ra Rb = a(b-**R**) a = (Rb)/(b-**R**)1 Answe

**r**s · Education & Reference · 01/11/2008**r**= 4 cscθ then**r**sinθ = 4. now,**r**cosθ = x, while**r**sinθ = y.... these a**r**e the equations needed to t**r**ansfo**r**m ca**r**tesian to pola**r**... thus you have y = 4. (a ho**r**izontal line) §1 Answe

**r**s · Science & Mathematics · 14/04/2008Let f:

**R**->**R**' be an isomorphism. If**R**is commutative, and a... of**R**', then a' = f(a) and b' = f(b) for some a,b in**R**. Then we have: a'b' = f(a)f(b) = f(ab) = f(ba) = f(b)f(a) = b'...2 Answe

**r**s · Science & Mathematics · 05/12/2012**r**^2+**r**=A/(2ph)? If so, then**r**^2+**r**-A/(2ph)=0=>**r**=[-1+/-sqrt(1+2A/(ph)]/2 =>**r**=[-1+sqrt(1+2A/(ph))]/2 or**r**=[-1-sqrt(1+2A/(ph))]/22 Answe

**r**s · Science & Mathematics · 20/09/2013Use the facts that sin(θ) = y/

**r**and**r**= √(x^2 + y^2). Fi**r**st, fo**r****r**= 3sin(θ):**r**= 3sin(θ)**r**= 3(y/**r**... is a ci**r**cle. In the subject line, I'll assume you mean**r**= sin(3θ) and not**r**= sin^3 (θ). You'll have to use a t**r**ig identity fo**r**...1 Answe

**r**s · Science & Mathematics · 19/05/2007**r**= 7(c - x)**r**/7 = 7(c-x)/7**r**/7 = c - x**r**/7 + x = c2 Answe

**r**s · Science & Mathematics · 16/02/2012(

**R**+ r )(**R**- r ) = A/pi**R**²-r² = A/pi <--- this is the difference of two squares method**R**² = A/pi + r²**R**= √(A/pi+r²)4 Answe

**r**s · Science & Mathematics · 26/04/2012

##### Ads

related to: R